FOSTERING STUDENT RESILIENCE THROUGH SUSTAINABILITY ACCOUNTING EDUCATION: EVIDENCE FROM HIGHER EDUCATION INSTITUTIONS - Sulbahri, Rifani Akbar (Catholic University Musi Charitas, 2026)
Purpose : This study examines the influence of Sustainability Accounting Education on student resilience in higher education. As the shift toward a green economy accelerates, students are expected not only to understand sustainability concepts but also to develop the psychological capacity to cope with academic challenges. Design Methodology Approach : Using a quantitative survey approach and simple linear regression, the findings show that SAE has a positive and significant effect on student resilience Findings :The study highlights the importance of embedding sustainability perspectives within accounting curricula to strengthen students’ adaptive capacities. Practical Implications : The novelty of this research lies in testing the direct relationship between SAE and student resilience an area that remains underexplored and in integrating Transformative Learning Theory, Education for Sustainable Development, and Cognitive Adaptation Theory as the conceptual foundation Originality Value : These results indicate that sustainability-oriented accounting education fosters reflective thinking, adaptive mindsets, and stronger student resilience.